A mouse retinal explant model for use in studying neuroprotection in glaucoma. (October 2016) - Pattamatta, Ushasree; McPherson, Zachary; White, Andrew
Abstract: The study aims to validate mouse retinal explants for use as an efficient tool to investigate neuroprotective therapies for treatment in diseases such as glaucoma. Eyes from C57BL/6 mice were enucleated immediately post-mortem to make two retinal explants per eye. Explants were cultured at an air/medium interface on membrane inserts for 7 days ex-vivo . Explants were treated either with Z-VAD-FMK (a pan-caspase inhibitor; 100 μM) or vehicle. Retinal Ganglion cell (RGC) density was analysed by βIII tubulin and RNA-binding protein with multiple splicing (RBPMS) immunohistochemistry. Caspase activity was measured using Caspase 3/7 glo assay and western blot. Caspase-3 expression was quantified using RT-PCR and western blotting. Retinal explants treated with Z-VAD-FMK demonstrated a 1.5-fold (p = 0.027) increase in number of surviving RGCs on day 4 compared to the control treatment using βIII tubulin staining. RGC viability was 2-fold (p = 0.002) higher in RGC stained with RBPMS on day 1 compared to control. There was no RBPMS staining of RGCs beyond day 1 in either treatment. The caspase activity was 4.75 and 5.5-fold (p = 0.002 and 0.004 respectively) higher in control as compared to treatment with Z-VAD-FMK on day 1, 2 respectively. Increase in caspase activity in control group was also confirmed by western blot for day 1 protein lysates. Caspase-3 mRNA expression was 4.75-fold higher in Z-VAD-FMK treated explants compared to control on day 1 (p < 0.001). Culture conditions appropriate to retinal explant culture for investigation of RGC apoptosis was identified. Retinal cultures at day 4 were ideal for detecting neuroprotection using βIII tubulin staining. RBPMS acts as a viability marker as well as to define best time point for investigation of apoptosis related signalling pathways which is day 1. These findings suggest that mouse retinal explants are good model for studying ganglion cell specific apoptosis and are applicable to diseases such as glaucoma. Highlights: Mouse retinal explants are good model for studying RGC specific apoptosis and are applicable to diseases such as glaucoma. Retinal cultures at day 4 were ideal for detecting neuroprotection using βIII tubulin staining. RBPMS act as a viability marker and defines best time point for investigation of apoptosis related pathways which is day 1.